Single antenna power measurement based direction finding under range-bounded rotation - Liang, Yunfeng. (2012)
In this report, the geo-location problem of multiple uncorrelated signal sources from single antenna power measurements while under translational movement is considered. In particular, we consider a geo-location scenario whereby the signal sources are located within a bounded region-of-interest (ROI) while the directional receiver is collecting the spatial diversity through received power measurements along predefined trajectories outside the ROI. For each trajectory, the receiver collected a vector of power measurements and we propose a technique to estimate the sources’ rough positions by adopting the earlier proposed single antenna power measurements based direction finding. These rough estimations are then updated with the refined estimations with the vector of power measurements obtained from the subsequent trajectories. The simulation results show superior performance as compared to a typical grid-search approach and the supposed method will be submitted for possible publication as a journal paper after more analysis on the results.